Evaluating the Accuracy of the 3-Sieve Particle Size Analysis Method Compared to the 12-Sieve Method - G. E. Bokelman; S. C. Stewart; A. L. Baldridge; J. C. Woodworth; S. S. Dritz; J. R. Kalivoda; C. R. Stark; C. K. Jones (Kansas Agricultural Experiment Station Research Reports, 2015)
The 3-sieve particle size analysis method was developed to estimate the particle size of ground grain within feed mills without the time and expense required for a 12-sieve analysis. The 3-sieve method is more simplistic because it is hand-shaken and uses fewer sieves but has drawbacks because it is not as precise as the 12-sieve method. Because shaking is not automated, technician variation may impact results. Furthermore, the accuracy of the original 3-sieve method has been questioned because the method was developed for corn between 400 to 1,200μm, and the industry now grinds various grains more finely. Some variations, such as changing the top sieve to a smaller diameter hole or using flow agent, may help improve its accuracy. In this instance, 420 grain samples were used to determine the impact of top sieve size, grain type, technician, and flow agent on the ability of a 3-sieve analytical method to accurately predict the mean particle size determined by a standardized 12-sieve method. The experiment was a 3 × 2 × 2 × 3 factorial with three technicians, two sieve sizes (U.S. No. 12 vs. 16 sieve as the top sieve), flow agent (0 vs. 0.5 g), and three grain types (corn, sorghum, or wheat). Prior to the experiment, all samples were analyzed according to the standard ASAE S319.4 method using a 12-sieve stack with a 15-min tap time and 1 g of flow agent. Linear regression was used to develop individual equations to predict the mean particle size for each of the 3-sieve methods compared to the standard 12-sieve method, and the GLIMMIX procedure of SAS was used to evaluate the impact main effects and interactions on prediction accuracy. All interactions were removed from the model due to insignificance (P>0.10). Technician, screen size, and flow agent did not affect the accuracy of the prediction equations. Grain was the only main effect of significance (P<0.05), where the prediction equation overestimated the particle size of wheat by approximately 15μm and underestimated the particle size of corn by approximately 12μm. While statistically significant, these variations were deemed to be sufficiently accurate for the 3-sieve method, and separate equations for each grain type were not warranted to retain the simplicity of the method. In summary, technician, sieve size, grain type, and the use of flow agent did not greatly affect the accuracy of the 3-sieve particle size analytical method, so the original method was concluded to be accurate and the preferred method.
Keywords: 3-sieve; analysis; grain; method; particle size